A STUDY ON INCLUSIVE PRACTICES AMONG HIGHER EDUCATION INSTITUTION FOR FOSTERING GENDER PARITY AMONG WORKFORCE IN URBAN BANGALORE - Anitha .B; Harini (International Journal of Research -GRANTHAALAYAH, 2025)
Women's education and empowerment are essential indicators of progress. Educated women contribute significantly to the Comprehensive development of the economy. According to the latest Global Peace Index (GPI) 2024, India is ranked 116th globally, improving from its previous ranking of 126th in 2023. However, a notable gap exists among universities in inclusive practices and gender parity. This study investigates inclusive practices within higher education institutions and their impact on fostering gender parity. Focusing on the perspectives of workforce, the research examines existing inclusive policies and practices and explores the lived experiences related to inclusivity and gender equity. Data collection methods include surveys and document analysis of institutional policies and reports at urban Bangalore college. Quantitative data will be analysed using descriptive and inferential statistics to identify regression and correlations between inclusive practices and gender parity outcomes. Qualitative data will be analysed to assess the existing practices and trends. The study aims to identify best practices, highlight challenges, and offer recommendations for higher education institutions to create more inclusive environments that promote gender parity and empower all members of the academic community. The findings will contribute to a deeper understanding of the factors influencing gender equity in academia and inform strategies for creating more equitable and inclusive institutions.